2012
DOI: 10.1007/s10531-012-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

Road mortality in freshwater turtles: identifying causes of spatial patterns to optimize road planning and mitigation

Abstract: Road mortality of freshwater turtles can be high enough to imperil populations near roads, thus there is a need to efficiently and accurately locate regions of excessive roadkill along road networks for mitigation. Weekly over 2 years, we drove a 160 km highway circuit in northeastern New York State, USA and recorded the location of all detected roadkill of three freshwater turtle species (Chelydra serpentina, Chrysemys picta, Emydoidea blandingii). We then analyzed the spatial dispersion of road-kill and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Based on the research conducted, it is likely that most species will not be impacted by a single factor. For example, among the studies to research freshwater turtles, two studies found that roads were a source of mortality due to wildlife-vehicle collisions [120,142] and two studies determined that the movement of turtles was physically hindered by the roads themselves [52,143]. Yet, it is the combination of both direct and indirect factors that will provide us with a better understanding of the barrier effects of roads on freshwater turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the research conducted, it is likely that most species will not be impacted by a single factor. For example, among the studies to research freshwater turtles, two studies found that roads were a source of mortality due to wildlife-vehicle collisions [120,142] and two studies determined that the movement of turtles was physically hindered by the roads themselves [52,143]. Yet, it is the combination of both direct and indirect factors that will provide us with a better understanding of the barrier effects of roads on freshwater turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended speeds vary from slower than 30 kmÁh À1 (e.g., Gomes et al 2009;Carvalho and Mira 2011;Santos et al 2011), 45-55 kmÁh À1 (e.g., MacKinnon et al 2005Barrientos and Bolonio 2009;Guinard et al 2012) to greater than 55 kmÁh À1 (e.g., Meunier et al 2000;Antworth et al 2005;Barthelmess and Brooks 2010). While detection of small vertebrate prey may be more reliable at slower speeds (Jackson 2003;Langen et al 2012), MacKinnon et al (2005 drove at 40-60 kmÁh À1 for detecting snake and turtle roadkill, Sutherland et al (2010) drove at up to 56 kmÁh À1 for the detection of amphibian roadkill, and Brockie et al (2009) drove at between 50-100 kmÁh À1 to detect animals of at least "rat size." However, none of these studies experimentally established the detection rate at the chosen speed (Erritzøe et al 2003), and based on our results, it is likely that 30 kmÁh À1 was suboptimal and time was wasted.…”
Section: Speed Trialsmentioning
confidence: 99%
“…; Langen et al . ; Cramer et al . ; Gunson & Teixeira ) seems logical considering that road mortality is a major impact of roads on wildlife and has stronger effects on population persistence than isolation (Forman & Alexander ; Jackson & Fahrig ).…”
Section: Introductionmentioning
confidence: 99%
“…, for owls; Langen et al . , for reptiles; Valero, Picos & Álvarez , for ungulates), or segments along the same road but with different traffic volumes (e.g. Coelho, Kindel & Coelho , for mammals, birds and reptiles; Boves & Belthoff , for owls; Garrah et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation